Comparison of Radiation Dose Achievements in Breast Cancer Patients for Variations of Irradiation Direction in Intensity Modulated Radiation Therapy (IMRT) - Elisabet Turnip,; Evi Setiawati,; Pandji Triadyaksa,; Mohamad Hidayatullah, (International Journal of Scientific Research in Science and Technology, 2025)
In the Treatment Planning System (TPS), when the patient is irradiated with one direction of radiation, the Organ At Risk (OAR) around the Planning Target Volume (PTV) receives a high dose and receives an uneven dose. By considering the dose distribution on the PTV and OAR, it is necessary to determine the appropriate radiation direction on the TPS. This study compares the radiation dose achieved by the PTV and OAR of breast cancer patients with radiation directions 3, 5, 7, and 9 on the TPS Intensity Modulated Radiation Therapy (IMRT). This study used 16 retrospective data sets of breast cancer patients consisting of 8 patient data without breast surgery and 8 post-breast surgery data. The data obtained in this study were V95, D2%, D50%, and D98% from the DVH graph. Data analysis was carried out by comparing the average values of the Conformity Index (CI) and Homogeneity Index (HI) and the average dose received by the OAR in four variations of radiation directions. In breast cancer patients without surgery, better CI values were obtained in 9 radiation directions with an average CI = 0.980424; the lowest CI value = 0.957054 and the highest CI value = 0.998541. While in post-operative breast cancer patients, better CI values were obtained in 7 radiation directions with an average CI = 0.983920; the lowest CI value = 0.928394 and the highest CI value = 0.999994. In breast cancer patients without surgery, better HI values were obtained in 9 radiation directions with an average HI = 0.153551; the lowest HI value = 0.086190, and the highest HI value = 0.209303. While in post-operative breast cancer patients, better HI values were obtained in 7 radiation directions with an average HI = 0.121777; the lowest HI value = 0.081539, and the highest HI value 0.158169. The mean dose received by OAR of breast cancer patients without surgery was achieved in 9 radiation directions. In contrast, in post-operative breast cancer patients, it was completed in 5, 7, and 9 radiation directions. Reviewed from the conformity factor (CI) and uniformity (HI), and the mean dose received by breast cancer patients, it can be concluded that planning using IMRT with 9 radiation directions is optimal for use in breast cancer patients without surgery. While radiation with 7 directions is optimal for use in post-operative breast cancer patients. With higher conformity, lower homogeneity, and PTV receiving the maximum dose, the dose received by OAR can be minimized.
Keywords: Breast cancer; number of radiation directions; IMRT; CI; HI